2014
DOI: 10.3409/fb62_4.301
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Leptin, NGF and Adiponectin in Metabolic Syndrome

Abstract: ATANASSOVA P., HRISCHEV P., ORBETZOVA M., NIKOLOV P., NIKOLOVA J., GEORGIEVA E. 2014. Expression of leptin, NGF and adiponectin in metabolic syndrome. Folia Biologica (Kraków) $ : 301-306. Adipose tissue secretes a variety of adipokines involved in the regulation of energy metabolism and insulin resistance. Metabolic syndrome corresponds to a clinical condition in which white adipose tissue is characterized by an increased production and secretion of inflammatory molecules which may have local effects on adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In addition, proteases secreted from activated monocytes and/or neutrophils cleave full-length adiponectin to generate globular adiponectin [36]. Supportively, blood NGF levels are upregulated in a group of women with obesity and the metabolic syndrome [26,27], while circulating adiponectin levels are lower in obese subjects [27]. Therefore, in an adipose tissue from obese subjects where inflammation develops, it is likely to occur that the amounts of NGF and full length adiponectin are increased and decreased, respectively and as a consequence dominance of NGF over adiponectin becomes clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, proteases secreted from activated monocytes and/or neutrophils cleave full-length adiponectin to generate globular adiponectin [36]. Supportively, blood NGF levels are upregulated in a group of women with obesity and the metabolic syndrome [26,27], while circulating adiponectin levels are lower in obese subjects [27]. Therefore, in an adipose tissue from obese subjects where inflammation develops, it is likely to occur that the amounts of NGF and full length adiponectin are increased and decreased, respectively and as a consequence dominance of NGF over adiponectin becomes clear.…”
Section: Discussionmentioning
confidence: 99%
“…NGF expression and secretion in 3T3-L1 adipocyte culture are markedly increased in response to inflammatory cytokine such as TNF [25]. Moreover, circulating NGF levels are upregulated in a group of women with obesity and metabolic syndrome, which are related to a low-grade systemic inflammation [26,27]. As NGF modulates various immune cell functions [28,29], it is likely that NGF plays roles as an inflammatory mediator in adipose tissues, in addition to roles as a neurotrophic factor.…”
Section: Introductionmentioning
confidence: 99%
“… 37 One study found that elevated plasma NGF levels in patients with MetS were considerably higher than in normal individuals. 10 It has been suggested that NGF can be involved in cellular function by initiating phosphorylation of the protein cascade. 38 NGF can also affect some metabolic conditions such as diabetes, obesity and MetS.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Recently, NGF and BDNF as adipokines are taken into consideration due to their possible roles in some metabolic disorders such as diabetes mellitus 6 , 7 , atherosclerosis 8 and metabolic syndrome (MetS). 9 Despite the contradictory results 10 , the growing body of evidence suggests that low levels of circulating BDNF and NGF were significantly associated with high body mass index (BMI), hemoglobin A1C (HbA1C) and hypertriglyceridemia. 11…”
Section: Introductionmentioning
confidence: 99%
“…Both WAT and BAT has been shown to express NGF and brain-derived neurotrophic factor (BDNF) in mouse (Sornelli et al 2009) and in human (Nisoli et al 1996, Peeraully et al 2004. And obesity was associated with an increase of NGF circulating level in women (Bullo et al 2007) and its expression in SAT (Atanassova et al 2014). Moreover, in a model of type 1 diabetes induced by streptozotocin injection in rat, NGF expression has been shown to increase in both WAT and BAT (Sornelli et al 2009).…”
Section: Nerve Growth Factor a Potential Marker Of Adipose Tissue Infmentioning
confidence: 99%